2016
DOI: 10.1016/j.theriogenology.2016.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic determinants and predictors of superovulatory yields in sheep: Circulating concentrations of reproductive hormones, ovarian status, and antral follicular blood flow

Abstract: Hormonal ovarian superstimulation has contributed to small ruminant reproduction around the world, impacting genetic improvement and zoosanitary programs, contributing to the conservation of endangered species, and supporting other related biotechnologies. Advanced knowledge surrounding the superovulatory treatments in sheep has resulted in enhanced control of influencing factors and improved the protocols currently used. However, in spite of minimization of some adverse factors, superovulatory responses in ew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 103 publications
(211 reference statements)
2
39
0
6
Order By: Relevance
“…This range of ovulatory responses was not due to the total pFSH dose used (100, 133 or 200 mg per ewe over 4 days; Figure , Table ). High variability in superovulatory outcomes is the major drawback of the MOET biotechnology in sheep; it has been attributed to several intrinsic and extrinsic factors (Bartlewski et al., ). Due to variable superovulatory responses and the fact that embryo collection in sheep is performed predominantly by a surgical technique (Fonseca et al., ), the ability to accurately and non‐invasively determine the outcome of hormonal superstimulation would be an invaluable asset.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This range of ovulatory responses was not due to the total pFSH dose used (100, 133 or 200 mg per ewe over 4 days; Figure , Table ). High variability in superovulatory outcomes is the major drawback of the MOET biotechnology in sheep; it has been attributed to several intrinsic and extrinsic factors (Bartlewski et al., ). Due to variable superovulatory responses and the fact that embryo collection in sheep is performed predominantly by a surgical technique (Fonseca et al., ), the ability to accurately and non‐invasively determine the outcome of hormonal superstimulation would be an invaluable asset.…”
Section: Resultsmentioning
confidence: 99%
“…A number of earlier studies suggested the existence of a relationship between the number of CL and circulating P 4 concentrations in cyclic ewes (Bindon, Chang, & Turner, ; Oyedipe, Pathiraja, Gyang, & Edqvist, ). There were no correlations between serum P 4 concentration and ovulatory responses in anoestrous Rideau Arcott sheep superovulated in a multiple‐dose pFSH regimen (Bartlewski et al., ; Fuerst et al., ). Similarly, Amiridis et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite efforts to improve superovulatory protocols (SOV) in sheep, variability in ovarian response remains the major limitation in multiple ovulation and embryo transfer (MOET) programs (Bartlewski et al., ). Thus, the CL are counted by laparoscopy to determine ovarian response and whether a surgical embryo recovery procedure is justified.…”
Section: Introductionmentioning
confidence: 99%